2011
DOI: 10.1002/crat.201000504
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐concentration oscillations of crystal‐solution phase equilibria in the presence of trace impurities of surface‐active agents

Abstract: Using the examples of aqueous salt solutions NaNO 3 , KNO 3 , RbNO 3 , K 2 SO 4 , NaBr . 2Н 2 О, KBr, and NН 4 NO 3 , it was experimentally proven that the new phenomena, i.e. temperature-concentration oscillations of crystal-solution phase equilibria detected previously in the range of 15-45 °С remain in the presence of trace impurities (10 -4 -10 -3 wt. %) of ion-active organic matters. The signs of breaks transformation into pair oscillations of "maximum-minimum" type are established for the K 2 SO 4 , NaBr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The author also found that C16H33NC5H5Br has a great effect on equilibrium temperature; in contrast, a trace impurity of polyvinyl alcohol hardly affects this. [55] In the same way, Franke et al [56] found that the NaNO3 solubility decreases exponentially when HNO3 is added and that the NaNO3 growth rate increases considerably.…”
Section: Crystal Growthmentioning
confidence: 85%
“…The author also found that C16H33NC5H5Br has a great effect on equilibrium temperature; in contrast, a trace impurity of polyvinyl alcohol hardly affects this. [55] In the same way, Franke et al [56] found that the NaNO3 solubility decreases exponentially when HNO3 is added and that the NaNO3 growth rate increases considerably.…”
Section: Crystal Growthmentioning
confidence: 85%